Evolution of Gas Cell Targets for Magnetized Liner Inertial Fusion Experiments at the Sandia National Laboratories PECOS Test Facility. (3rd April 2018) - Paguio, R. R.; Smith, G. E.; Taylor, J. L.; Tomlinson, K.; Holt, R. R.; Tatum, W. D.; Farrell, M. P.; Betcher, J.; Harvey-Thompson, A.; Geissel, M.; Kellogg, J.; Peterson, K.
Abstract: Z-beamlet experiments conducted at the PECOS test facility at Sandia National Laboratories (SNL) investigated the nonlinear processes in laser plasma interaction (or laser-plasma instabilities) that complicate the deposition of laser energy by enhanced absorption, backscatter, filamentation, and beam-spray that can occur in large-scale laser-heated gas cell targets. These targets and experiments were designed to provide better insight into the physics of the laser preheat stage of the Magnetized Liner Inertial Fusion scheme being tested on the SNL Z-machine. The experiments aim to understand the trade-offs between laser spot size, laser pulse shape, laser entrance hole window thickness, and fuel density for laser preheat. Gas cell target design evolution and fabrication adaptations to accommodate the evolving experiment and scientific requirements are described in this paper.